اخلاقيات مهنة المحاسبة و دورها في مصداقية القوائم المالية - أحمد طالبي; محمد الهادي طويل; بشير فريجات; طارق حوامدي (university of eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى الوقوف على أهمية وجود أخلاقيات مهنة المحاسبة وتأثيرها على خاصية الملاءمة والمصداقية وبالتالي مدى تأثيرها على جودة القوائم المالية. ولتحقيق هدف الدراسة تم توزيع استبيان على عينة من مهنيي المحاسبة من ثلاث ولايات (الوادي, بسكرة, ورقلة), وحلِّلت باستخدام الاختبارات والمعالجات الإحصائية المناسبة خلصت إلى أنه لدى أفراد العينة وعي بأهمية أخلاقيات مهنة المحاسبة وتأثيرها على وظيفة المحاسب وبأنه لأخلاقيات مهنة المحاسبة دور مهم وتأثير كبير على مصداقية وجودة القوائم المالية. This study aims to determine the importance of the existence of ethics in the accounting profession and its impact on the characteristic of suitability and credibility, and thus the extent of its impact on the quality of financial statements. To achieve the aim of the study, a questionnaire was distributed to a sample of accountants from three states (ELoued, Biskra, Ouargla), and it was analyzed using appropriate tests and statistical treatments. It was concluded that the sample members have an awareness of the importance of the ethics of the accounting profession and its impact on the accountant’s job, and that the ethics of the profession Accounting has an important role and has a major impact on the credibility and quality of financial statements.
مذكرة ماستر محاسبة
Keywords: أخلاقيات; مهنة المحاسبة; المصداقية; القوائم المالية; ethics; accounting profession; credibility; financial statements